SCALES OF PREJUDICE TOWARD THE CHARACTERS AS PORTRAYED IN ZOOTOPIA FILM - Anugerah, Resky Ainun Juni; Surya, Satyawati; Asanti, Chris (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This research analyzed about the stages of prejudice in Zootopia film. The purpose of this research is to identify the prejudice stages represented by the characters in the film. This research used Gordon Allport is theory of the stages of prejudice which are divided into 5 stages, namely; (1) Antilocutin, (2) Avoidance, (3) Discrimination, (4) Physical attack, and (5) Extermination. The method of this research is content analysis with a qualitative approach. The data used in this research are dialogues, utterances, actions, and situations description that related to the research question. Based on the analysis, the researcher found that all of the prejudice stages portrayed trough film by almost all of the characters, but the most of prejudice stages that portrayed and found is discrimination. Hence, it can be concluded that discrimination as one stage of prejudice is prove to be done by majority group.